Chemically Induced Cell Wall Stapling in Bacteria. Issue 2 (18th February 2021) - Rivera, Sylvia L.; Espaillat, Akbar; Aditham, Arjun K.; Shieh, Peyton; Muriel-Mundo, Chris; Kim, Justin; Cava, Felipe; Siegrist, M. Sloan
Summary: Transpeptidation reinforces the structure of cell-wall peptidoglycan, an extracellular heteropolymer that protects bacteria from osmotic lysis. The clinical success of transpeptidase-inhibiting β-lactam antibiotics illustrates the essentiality of these cross-linkages for cell-wall integrity, but the presence of multiple, seemingly redundant transpeptidases in many species makes it challenging to determine cross-link function. Here, we present a technique to link peptide strands by chemical rather than enzymatic reaction. We employ biocompatible click chemistry to induce triazole formation between azido- and alkynyl-d -alanine residues that are metabolically installed in the peptidoglycan of Gram-positive or Gram-negative bacteria. Synthetic triazole cross-links can be visualized using azidocoumarin-d -alanine, an amino acid derivative that undergoes fluorescent enhancement upon reaction with terminal alkynes. Cell-wall stapling protects Escherichia coli from treatment with the broad-spectrum β-lactams ampicillin and carbenicillin. Chemical control of cell-wall structure in live bacteria can provide functional insights that are orthogonal to those obtained by genetics. Graphical Abstract: Highlights: The bacterial cell wall is crosslinked by d -amino acid-containing peptides β-Lactam antibiotics interfere with cell-wall crosslinking We developed a d -amino acid-based method for introducing synthetic crosslinks The crosslinks protect Escherichia coli from broad-spectrum β-lactam antibiotics Abstract : We developed a chemical method for introducing synthetic cross-links into the cell walls of live Gram-positive and Gram-negative bacteria. The cross-links protect Escherichia coli from broad-spectrum β-lactam antibiotics. Chemically induced cross-linking complements genetics as an independent way to investigate the physiological roles of cell-wall connectivity.